Influence of Lithium and Lanthanum Treatment on TiO2 Nanofibers and Their Application in n‐i‐p Solar Cells. Issue 14 (29th April 2019) - Ambroz, Filip; Sathasivam, Sanjayan; Lee, Roxanna; Gadipelli, Srinivas; Lin, Chieh‐Ting; Xu, Shengda; Poduval, Radhika K.; Mclachlan, Martyn A.; Papakonstantinou, Ioannis; Parkin, Ivan P.; Macdonald, Thomas J.
Abstract: The addition of cations to TiO2 photoelectrodes is routinely accepted as a route to enhance the performance of conventional n‐i‐p solar cells. However, this is typically achieved in multiple steps or by the incorporation of expensive and hydroscopic cationic precursors such as lithium bis(trifluoromethanesulfonyl)imide. In addition, it is often unclear as to whether the incorporation of such cation sources is inducing "doping" or simply transformed into cationic oxides on the surface of the photoelectrodes. In this study, TiO2 nanofibers were produced through a simple electrospinning technique and modified by introducing lithium and lanthanum precursors in one step. Our results show that the addition of both cations caused minimal substitutional or interstitial doping of TiO2 . Brunauer‐Emmett‐Teller measurements showed that lanthanum‐treated TiO2 nanofibers had an increase in surface area, which even exceeded that of TiO2 P25 nanoparticles. Finally, treated and untreated TiO2 nanofibers were used in n‐i‐p solar cells. Photovoltaic characteristics revealed that lanthanum treatment was beneficial, whereas lithium treatment was found to be detrimental to the device performance for both dye‐sensitized and perovskite solar cells. The results discuss new fundamental understandings for two of the commonly incorporated cationic dopants in TiO2 photoelectrodes, lithium and lanthanum, and present a significant step forward in advancing the field of materials chemistry for photovoltaics. Abstract : n‐i‐p it in the bud : The addition of lithium and lanthanum cations is shown to cause minimal substitutional or interstitial doping of TiO2 . Brunauer‐Emmett‐Teller measurements show that lanthanum‐treated TiO2 nanofibers had an increase in surface area, which even exceeded that of TiO2 P25 nanoparticles. Finally, treated and untreated TiO2 nanofibers are used in n‐i‐p solar cells. Photovoltaic characteristics reveal that lanthanum treatment is beneficial, whereas lithium treatment is found to be detrimental to the device performance for both dye‐sensitized and perovskite solar cells.